Producción, oficios y migración en San Rafael de Heredia: un análisis del censo poblacional de 1927 - Torres Hernández, Margarita (1991)
This article focuses on the social/occupational structure in agriculture, as regards the area of San Rafael Heredia and migrants toward the northwestern Central Valley, in light of information from the 1927 population census manuscripts.